Pop Up Book Based on Ethnomathematics Effectively Improves Mathematical Knowledge Competence - Sawitri, Ni Wayan; Wiarta, I Wayan; Wulandari, I Gusti Agung Ayu (International Journal of Language and Literature, 2024)
Lack of interactive and varied learning media on the material of arithmetic operations of whole numbers in Mathematics subjects, and the teaching materials used are only sourced from books. This makes the learning outcomes of students less than optimal. This study was conducted to develop pop-up book learning media that are adjusted to students' needs through the application of ethnomathematics-based learning models. This study aims to determine the design, feasibility, and effectiveness of the use of pop-up book learning media based on ethnomathematics in learning mathematics on arithmetic operations of whole numbers for grade III of elementary school. The model used in the development of this media is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The data collection technique uses a test with a short answer instrument. The results of the study showed that the mathematics pop-up book is feasible and practical to be applied in the learning process, as evidenced by the feasibility test from the results of the design expert test 90%, content experts 90%, learning design experts 90%, learning media experts 92%, individual tests 88%, small group tests 91%. The results of the effectiveness test calculation obtained a t count (4.640), which is greater than the t table (1.967), so Ha is accepted. Thus, it can be concluded that pop-up book learning media based on ethnomathematics is feasible to be applied to the mathematics lesson content, especially the material on arithmetic operations of whole numbers for grade III of elementary school.